2012
DOI: 10.1111/j.1654-1103.2012.01475.x
|View full text |Cite
|
Sign up to set email alerts
|

Limited effects of dominant species population source on community composition during community assembly

Abstract: Question To what extent do dominant species population sources and subordinate species pools affect diversity and composition of an assembling grassland community? Location Illinois, USA. Methods Percentage cover of all species were recorded annually in 36 1‐m2 quadrats assigned to a factorial combination of dominant species population source (functionally distinct cultivar or non‐cultivar seed source) and designed species pool (three levels varying in species identity, but with equal functional group represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 55 publications
3
46
0
Order By: Relevance
“…The notion that genotypic diversity of a dominant species provides a source of diversifying selection within the plant community is consistent with other grassland studies [51], [52]. Gibson et al [44] and Baer et al [42] demonstrated no strong effect of dominant grass source on community diversity and ecosystem processes for the first four years of community establishment from this field experiment. Similar diversity and functioning of communities sown with the different grass sources was attributed to the high productivity of subordinate species (i.e., a dilution effect), close proximity of the germplasm of the S. nutans cultivar to the local ecotype, and strong filtering of environment or site effects [42], [44].…”
Section: Discussionsupporting
confidence: 89%
“…The notion that genotypic diversity of a dominant species provides a source of diversifying selection within the plant community is consistent with other grassland studies [51], [52]. Gibson et al [44] and Baer et al [42] demonstrated no strong effect of dominant grass source on community diversity and ecosystem processes for the first four years of community establishment from this field experiment. Similar diversity and functioning of communities sown with the different grass sources was attributed to the high productivity of subordinate species (i.e., a dilution effect), close proximity of the germplasm of the S. nutans cultivar to the local ecotype, and strong filtering of environment or site effects [42], [44].…”
Section: Discussionsupporting
confidence: 89%
“…; Wilsey ; Lambert, Baer & Gibson ; Gibson et al . ; Grman, Bassett & Brudvig ). Therefore, the inclusion of non‐local seeds with enhanced competitive physiologies may reduce species diversity.…”
Section: Discussionmentioning
confidence: 99%
“…; Middleton, Bever & Schultz ; Wilsey ; Gibson et al . ). Maladaptations in the ecological properties of a dominant species may have cascading effects through the community (Rogers & Montalvo ).…”
Section: Introductionmentioning
confidence: 97%
“…In practice, species and trait diversity should be regarded separately as subordinate species may make a proportionally larger contribution to the functioning of ecosystems than would be expected (e.g. from biomass) compared to dominant species (O'Gorman & Emmerson, 2009;Gibson et al, 2013). This may be particularly important for wet grasslands, where plants of small stature contribute substantially to species richness and nature conservation value (e.g.…”
Section: Mechanisms For Plant Community Resiliencementioning
confidence: 99%